EVALUATION OF PHYSICAL ACTIVITY OF FUTURE SPEECH THERAPISTS IN THE CONTEXT OF DEVELOPING THE HEALTH CARE COMPETENCE OF A SPECIALIST - Головченко, Олексій (SWorldJournal, 2024)
In order to evaluate the level of physical activity of students of the specialty 016.01 Special education Speech therapy, as a component of the health-preserving competence of the future specialist, an assessment of the physical activity of 22 students a